143k views
3 votes
Explain how to solve 3x − 4 = 6 using the change of base formula log base b of y equals log y over log b. Include the solution for x in your answer. Round your answer to the nearest thousandth.

User Carlost
by
5.8k points

1 Answer

5 votes

Answer:


x \approx 2

Explanation:

The given equation is


3^(x)-4=6

First, we move all constant terms to one side


3^(x)=6+4\\ 3^(x)=10

Observe that the bases are different, so first, we rewrite the expression as logarithm


x=log_(3)(10)

But, we need a logarithm with base 10, so we apply the following property


log_(a)(b)=(log(b))/(log(a))


x=(log(10))/(log(3))

But,
log(10)=1

So,


x=(1)/(log(3)) \approx (1)/(0.50) \approx 2

User Eftekhari
by
5.7k points